The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1965
DOI: 10.1021/j100885a037
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Aqueous Salts with High Area Aluminas

Abstract: The coupled or equivalent exchange of the cations and anions of 11 salts, chiefly alkali metal and alkaline earth chlorides, with surface Hf and OH-of a commercial a-basic aluminum oxide was studied. Adsorption equilibrium constants and reaction site densities are reported. These site densities and those for two salts with other aluminas are low, so that the area per site is of the order of 1-10 X lo2suggesting the reaction is very specific.In three other systems which are a t least partially irreversible (whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1968
1968
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…However, recent works [26,27,36,[42][43][44]711 devoted to the anchoring/grafting in vapor phase (CVD) (see Sections 4.1.2.3 and 4.1.2.4). Some studies suggest that they are less reliable for obtaining species as well-defined as with ally1 precursors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent works [26,27,36,[42][43][44]711 devoted to the anchoring/grafting in vapor phase (CVD) (see Sections 4.1.2.3 and 4.1.2.4). Some studies suggest that they are less reliable for obtaining species as well-defined as with ally1 precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Lateral interactions between adsorbed ions (ion coadsorption) have been reported [27,281 and make questionable the use of mass action equations at interfaces. In particular, lateral interactions between adsorbed ions, site heterogeneity as well as phenomena involving the oxide dissolution or rehydration are not taken into account systematically.…”
Section: A Types Of Ion Exchangersmentioning
confidence: 99%
“…Lateral interactions between adsorbed ions (ion coadsorption) have been reported [27,28] and make questionable the use of mass action equations at interfaces. In particular, lateral interactions between adsorbed ions, site heterogeneity as well as phenomena involving oxide dissolution or rehydration are not systematically taken into account.…”
Section: A Surface Charges and Their Consequencesmentioning
confidence: 99%
“…As a consequence, complexation of dissolved Al(III) by molybdenum resulted in extensive dissolution of the alumina support, even at pH-values close to neutrality. Surface-selective 27 Al CP-MAS solid-state NMR showed that these species are not only formed in solution but also deposited on the support, and are thus the real precursors of the molybdic species present in the finished catalyst. Surface-selective 27 Al CP-MAS solid-state NMR showed that these species are not only formed in solution but also deposited on the support, and are thus the real precursors of the molybdic species present in the finished catalyst.…”
Section: The Support As a Chemical Reactantmentioning
confidence: 99%
“…The ion-exchange properties of the hydrous alumina have been extensively studied (16)(17)(18)(19) and depend upon the pH of the ion-exchange medium. At pH values greater than the isoelectric point (iep) Le., 6.8 for y-alumina, the oxide behaves as a cation exchanger, while below the iep it possesses anion exchange properties.…”
Section: Alumina Chloroaluminamentioning
confidence: 99%